Drug Prescription Patterns in Older People Residential Homes - Malihe Saboor; Mahshid Foroughan; Farahnaz Mohammadi Shahbalaghi (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: Compared to other age groups, older people, especially frail older people residing in nursing homes use medications more due to the higher prevalence of chronic diseases. This study aimed to investigate prescription patterns for older people in nursing homes of Tehran in 2011. Methods & Materials: In this cross-sectional study, the data of 170 older people, sampled random cluster gathering method, using medical records, questionnaires and interview with nurses and physicians. The data analyzed using descriptive statistics including mean, distribution, Chi-square, t-test, Fisher, and SPSS version 16 (P<0.05). Results: The mean average age of the sample was 79.75±2.4% of them were female. 62.4% received more than 5 types of medicines. The mean number of medicines was 7.55 with the ranging of 1-19 drugs. The most medicine forms used by older people were: tablets 98.2%, injection medicines 20.6 %, drops 13.5%, syrup 8.8%, sprays 6.5%, ointments and suppositories 2.9%. The following medicines were used the most used among older people respectively: Central Nervous System drugs, vitamins, cardiovascular drugs, hematologic and gastrointestinal drugs. Vitamins (81.2%), ASA (37.64%), Alprazolam (22.35%) were the most used drugs. There was not a significant relationship between participating in geriatric educational course And the mean numbers of the prescribed medications (P=0.054)., as well as between covering by health insurance specialty in medicine and the mean of the numbers of mediations (P=0.068). There was a significant relationship between having insurance and the mean number of prescribed medicine (P=0.05). Conclusion: Developing educational programs on geriatric pharmacology general practitioners and more supervision on residential care homes practices may have affects on prescription pattern.